No-quenching baseline for energy loss signals in oxygen-oxygen collisions - Gebhard, Jannis; Mazeliauskas, Aleksas; Takacs, Adam (Journal of high energy physics, 2025)
In this work, we perform computations of inclusive jet, and semi-inclusive jet-hadron cross sections for minimum bias oxygen-oxygen collisions at RHIC and LHC collision energies. We compute the no-quenching baseline for the jet nuclear modification factor RAA and jet-, and hadron-triggered semi-inclusive nuclear modification factors IAA. We do this with state-of-the-art nuclear parton distribution functions (nPDFs), next-to-leading-order matrix elements, parton shower, and hadronization. We observe deviations from unity due to cold-nuclear matter effects, even without quenching. We demonstrate that the parton distribution uncertainties constitute a significant obstacle in detecting energy loss in small collision systems. Hadron-triggered observables are particularly sensitive to uncertainties due to correlations between the trigger and analyzed particles. For jet-triggered IAA, there exists a kinematic window in which nPDF and scale uncertainties cancel dramatically while showing little sensitivity to parton shower and hadronization models, addressing a major limiting factor for energy loss discovery in small systems.
Gesehen am 10.12.2025